The role of angiogenesis inhibitors associated with tyrosine kinase inhibitors in the first-line treatment for EGFR-mutated advanced lung cancer - Motta-Guerrero, R (2024)
Tyrosine kinase inhibitors (TKIs) are the standard treatment for epidermal growth factor receptor mutant (EGFRm) advanced non-small cell lung cancer (NSCLC). Combining TKIs with an angiogenesis inhibitor has shown promise in pre-clinical studies. A systematic search of clinical trials found that combining erlotinib (a first-generation TKI) with bevacizumab or ramucirumab (angiogenesis inhibitors) improved progression-free survival (PFS) in EGFRm advanced NSCLC patients compared to TKI alone. However, no significant benefit in overall survival (OS) was observed in trials. Similar efficacy was seen in patients with specific EGFR mutations. Third generation TKIs were used as second-line therapy for patients with the T790M mutation. The combination treatment was associated with a higher incidence of severe adverse events. Overall, combining erlotinib or another TKI with an angiogenesis inhibitor is a safe and effective alternative for first-line treatment in EGFRm advanced NSCLC, particularly in countries without access to osimertinib and for patients with the EGFR L858R mutation.